Construction and Properties of Ripples on Polymers for Sensor Applications - Svorcik, Vaclav; Nedela, Oldrich; Slepicka, Petr; Lyutakov, Oleksiy; Slepickova Kasalkova, Nikola; Kolska, Zdenka (Manufacturing Technology Journal, 2018)
Surface modification of polystyrene and polyethylene naphthalate by a KrF pulse excimer UV laser under the angles of incidence of the laser beam in the range of 0 to 60° with a step of 7.5° was studied in this paper. The influence of the angle of incidence on the period of the resulting surface structures and the modified refractive index of the substrates was determined with all the other parameters of the laser radiation held constant. All data was acquired on the basis of surface analysis. Atomic force microscopy was used to study the morphological changes in the laser treated samples and to determine the period of the ripple-like surface structures, from which the modified refractive index was subsequently calculated. Selected samples were metallized with gold with aim to determine the influence of patterned substrate on consequently formed nanolayer. These information may be useful for consequently constructed SERS system based on ripple-metal system.
Keywords: Polystyrene; Polyethylene naphthalate; Laser treatment; Microscopy; Polymer; Periodic nanostructures